DOES THE WESTERNISATION OF DIET AFFECT FOOD SECURITY IN NIGERIA? EVIDENCE FROM FAST FOOD AND STREET FOOD CONSUMPTION IN THE DUTSE METROPOLIS, JIGAWA STATE - AHUNGWA, G. T; GAMA, E. N; TERAN, D. A; MUHAMMAD, M. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2022)
The study examined the westernisation of diet vis-à-vis the consumption of fast food (FF) and street foods (SFs) and their implication on food security in Dutse Metropolis, Nigeria. Using a multistage sampling procedure, 118 patrons of FF and SFs were selected from eight quick service restaurants (QSRs) and data were collected using an interview schedule. Descriptive statistics and cost-of-calorie function were used as tools of data analysis. Results revealed that most respondents were male (66.1%), the majority were aged 21 - 40 years (81.4%), single (71.2%), and educated (96.6%). Evidence of the westernised dietary pattern was manifold in four facets: growing consumption of food products from supermarkets and food vendors (origin of food), the diet of animal-source, diet drinks, and sugar or artificial sweeteners (food ingredients), high consumption of fast food, soft drinks and processed foods (food processing) and consumption of takeaway, ready-prepared meals, fried foods and microwave foods (food preparation technique). Further analysis showed that the westernisation of diet is driven by the high prices of food (traditional foodstuffs), rapid urbanization growth and urban lifestyle, and technological advancement in food systems. The cost-of-calorie analysis reveals that the amount of calorie consumption is significantly influenced by income expenditure on food (R2 = 0.925, p < 0.000). Food expenditure analysis showed that 58.5% of FF and SFs consumers were food insecure with an expenditure deficit of N1, 850/person/day to acquire the recommended calorie threshold of 2,200kcal/person/day. Findings attest that the Dutse metropolis is enmeshed in the web of dietary transition that if not checked, could erode the gains of the traditional food system. Thus, practices such as home-grown food culture are recommended as measures of the current trend of overt dependence on food markets.